Associação da ocorrência de cianobactérias às variações de parâmetros de qualidade da água em quatro bacias hidrográficas de Minas Gerais - Hanna Duarte Almeida Ferraz (2012)
The presence of cyanobacteria in water systems is one of the main pollution problems all over the world. A deep concern is dedicated to cyanobacterial blooms in Brazil, since it was the first country in the world to register human deaths caused by the presence of cyanoprocaryota toxins. Despite this rising problem the investigation of cyanobacterial presence in river waters is quite limited to the international literature. The aim of this study is to understand the associations between water quality parameters and the occurrence of high cyanobacteria density in lotic environments of Minas Gerais State. Water quality data used in this research refers to a long term monitoring programme carried out in the State of Minas Gerais, Brazil by IGAM. Four drainage basins, which are characterized by a marked anthropic influence, have been selected. Data of cyanobacteria populations were considered in the period 2007-2011, with a total of 1555 samplings. The Followingwater parameters were analyzed: cyanobacteria density, chlorophyll a, temperature, dissolved oxygen, BOD, pH, chlorine, colour, alkalinity, electrical conductivity, nitrate, nitrite, ammonium nitrogen, total phosphorus, turbidity and total suspended solids. The statistical evaluation involved the detection of outliers, testing the normality of the data, Spearman correlation matrix and Principal Component Analysis (PCA). Seven cyanobacteria taxa have been identified as responsible for blooms registered in the four drainage basins. Its important to notice that some of those species are able to produce cyanotoxins, what makes their monitoring even more important. Most of the cyanobacteria blooms were registered during the dry season (April to October). This evidence may be a discussion point about the influence of global warming in the onset of cyanobacterial blooms. PCA results point out a positive correlation of Cyanobacteria Density with pH, Chlorophyll a, Nitrate and Temperature and an inverse relationship with Colour, Turbidity and Suspended Solids. The Velhas basin was the one with major high density episodes occurrences in the period of study and that was due to its long term high values of nitrate, phosphorus and pH. The paramount conclusion to be drawn from this research is that it takes more than one main trigger for the onset of cyanobacteria blooms in Minas Gerais State rivers. The combination of following factors: high loads of nitrate and phosphorus, alkaline pH values, high water temperatures and the prevalence of long dry periods is what takes for the rise of cyanobacteria density.